Schooling Investments and Macroeconomic Conditions: A Micro-Macro Investigation for Latin America and the Caribbean - Suzanne Duryea; Jere R. Behrman; Miguel Székely (Inter-American Development Bank, Office of the Chief Economist, 1999)
Schooling is a major factor in economic development. There is extensive empirical literature on what determines schooling attainment. But most of this literature uses micro data to explore connections between schooling attainment and family background and experiences, local markets, local schools and other community characteristics. These studies generally have not linked schooling attainment closely to changes in aggregate economic conditions. This paper uses a new high quality data set for 18 Latin American and Caribbean countries to assess the effects of macro conditions on schooling attainment. Household survey data are used to construct a quasi panel with information on attainment for birth cohorts born between 1930 and 1970, which is merged with country-specific aggregate data. We use the data to document schooling progress in Latin America and estimate multivariate relations for schooling attainment by birth cohorts as related to sets of variables for macroeconomic stability, factor endowments, demographic developments, institutions and culture and religion. These estimates are used to decompose the change in schooling progress by decade, and to explore the causes of the slowdown in schooling accumulation in the region since the 1980s debt crisis.
Keywords: 330; Bildungsinvestition; Allgemeinbildende Schule; Entwicklung; Lateinamerika